Uso do data mining no estabelecimento de relacionamentos entre medidas de desempenho. - Custodio, Flavio Augusto (2004)
This work aims to propose a method to analyze the relationships between performance measures in a Performance Measurement System using historical performance data storaged in a datawarehouse or operational data store. There is a problem in the performance measurement area that it doesn t have methods to create relationships models between performance measures. The present methods that we have in academic researches don t help to build the relationships concerning historical performance data. Therefore, there is a trend to build the relationship between performance measures to reflect the desirable future, but it is also true that we have to learn about the past actions. Nowadays, with the increasing complexity in the organizations environment it is very difficulty to handle historical data about performance to identify relationship patterns without using concepts, techniques and tools of the Information Technology (IT) field. The variables contained in the performance measurement models are increasing continually so it is important to understand the complex net of relationships between performance measures in an organization. The stakeholders in the organization see the relationships between performance measures as trivial, but this doesn t help because the relationships are partial and subjective and the stakeholders that articulate the variables in most of the cases are accountable by the performance. It s expected that decision makers participate and share their models of relationships between performance measures and that it be the most comprehensive as possible. This work is important because it proposes to use the data mining philosophy to help building a method to understand relationship between performance measures with performance historical data. Hence, it will be possible to define and communicate the relationships between performance measures to the users of the organization and increase the use of performance measurement models. The proposed method presents a process to build and find relationships between performance measures data using data mining techniques. The IDEF0 procedure was used to present our approach.